Mídias locativas em narrativas urbanas artísticas e culturais - Araújo, Daniel Paz de (2012)
Through the mobile networks, we have the constant possibility of connecting to different places, people and cultures, being able to expand awareness and act directly on the physical and virtual environment that we operate. The material elements located in a space / time becomes overlaid with informational layers of different media produced by individuals or groups independently. Browse through interfaces such networks, systems and streams is one of the contemporary s dilemmas. Given the new space-time relationships on which forms of artistic and cultural expression have been appropriate, the objective of this paper is to analyze and generate transmedia narratives productions within the creative design, and how it is possible to produce, distribute and consume information movably through locative media, in a simple, practical and low cost, enabling hybrid interactions within physical and virtual territory. This will be carried out joint artistic-technological narratives between this work and artists who works with different forms of expression, either spatially and / or time through imagery, sound or verbal. To this end, relations between this work with the project iD Bairo SP # 02 and the Winter Festival of Ouro Preto and Mariana 2011, provided the cultural and artistic products being transposed into cyberspace, through its concentration and diffusion by various digital medias, simply, free of charge and with the possibility of expansion by the cooperation of other artists, fans and stakeholders in general